Marfan's syndrome - inheritance, diagnostic methods, management in disease - Kinga Grużewska-Piotrowska; Monika Pająk; Joanna Hubka; Wojciech Wcisło (Nicolaus Copernicus University in Toruń, 2023)
Introduction: Marfan's syndrome (MFS) is a systemic, autosomal dominant connective tissue disease. It is caused mainly by the mutations in the FBN1 gene and is connected with extracellular matrix protein fibrillin-1. The incidence is about 2-3 per 10 000. About 70-75% of cases are inherited in an autosomal dominant fashion and the remaining are de-novo mutations. The aim of the study: This study aims to gather current knowledge about inheritance, diagnostic methods and management in Marfan syndrome. Materials and methods: This review was based on available data collected in the PubMed database and Google Scholar web search engine, using the key words: Marfan's syndrome. MFS, FBN1, aortic aneurysm, Marfan Foundation Conclusion: The diagnosis of Marfan's syndrome requires detailed assessment of the body build, concomitant diseases and, above all, genetic history of the patient. Connective tissue mutations can develop at any time, and already existing defects can exacerbate. Physicians should pay particular attention while examining patients with suspected MFS. Already diagnosed patients should be checked regularly to quickly find possible complications. There is no casual treatment, multidirectional preventive therapeutic treatment is used.